Multimorbidity Among Urban Poor in India: Findings From LASI, Wave-1 - Sinha, Abhinav; Kerketta, Sushmita; Ghosal, Shishirendu; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Public Health, 2022)
Background Multimorbidity has become a norm in low-and-middle income countries such as India requiring notable health system improvements to combat. Urban population is a heterogeneous group where poor are at a risk of facing inequity in accessing healthcare services which can jeopardize our efforts to attain universal health coverage (UHC). We aimed to estimate the prevalence, assess correlates and patterns of multimorbidity among urban poor. Further, we assessed the outcomes of multimorbidity such as healthcare utilization, expenditure and self-rated health. Methods Longitudinal Ageing Study in India (LASI), wave-1 is a nationally representative survey conducted amongst ≥45 years in 2017-19. We included 9327 participants residing in urban areas, categorized as poor based on monthly per capita expenditure. Descriptive statistics computed prevalence with 95% uncertainty interval. Multivariable logistic regression was executed to assess the association between multimorbidity and various correlates, expressed as adjusted odds ratio. An ordinal regression model was run between self-rated health and number of chronic conditions. Results The prevalence of multimorbidity was 45.26% among the urban poor. Hypertension and oral conditions were the most commonly observed dyad. Respondents who were poorer [AOR: 1.27 (1.06-1.51)] had higher chances of having multimorbidity than the poorest. Respondents with a health insurance [AOR: 1.40 (1.14-1.70)] had a higher risk of having multimorbidity. In-patient admission was significantly higher among participants having multimorbidity. Out of pocket expenditure increased while self-rated health deteriorated with each additional morbid condition. Conclusion Multimorbidity is found to be increasingly prevalent among urban poor and individuals having health insurance which demonstrates the need to expand healthcare insurance schemes such as Ayushman Bharat for urban poor to achieve UHC.